Experimental investigation of the unclogging process of propped fractures with dynamic stimulation: influence of the proppant and of the dynamic signal - Youssef Fawaz; Christian La Borderie; Antoine Jacques; Gilles Pijaudier-Cabot (Open Geomechanics)
Dynamic excitation of reservoir systems trapping hydrocarbons is a potentially promising solution for increasing the production. At the laboratory scale, it was found that a dynamic vibration of the fluid pressure could induce an increase in permeability of fractures and improve the flow in the drainage system. This phenomenon was also confirmed on sites by the rise in water and oil well production following seismic events. In both cases, it has been hypothesized that the fluid pressure oscillations could contribute to breaking clusters of fine particles located in fractures that clog drains in the reservoir. In order to confirm such an assumption, we developed in a previous study experiments aimed at reproducing clogging in propped fractures and unclogging due to dynamic loads applied perpendicularly to the fracture (Fawaz et al., 2021). This paper built on this experimental set-up and presents a study of the major parameters governing the unclogging of propped fractures by dynamic stimulation. The influences of the proppant distribution density, proppant size, amplitude, and of the frequency of the signal were studied. After applying the dynamic load, results showed a significant increase in permeability with a high recovery rate reaching 75%.